Healthcare and forensic medical aspects of police detainees, suspects and complainants in Europe. (July 2018) - Heide, Steffen; Chariot, Patrick; Green, Peter; Fabian, Jana; Payne-James, Jason
Abstract: Death and harm is well-recognised in detainees in police custody worldwide. Based on the results of previous global surveys and the CPT (European Committee for the Prevention of Torture) recommendations a questionnaire was developed to summarise the current medical aspects of police custody in European countries. The survey was distributed to named contacts in all European countries. Data from 25 European countries was obtained. The results reveal significant differences in the regulations among the different countries, with nothing close to a harmonised European standard in place at present. This study has identified interesting variations in the methods and standards of healthcare and forensic medical services to detainees in police custody (e.g. quantitative mode of monitoring, qualification of the doctors, maximum time allowed for holding a detainee in police custody, body or an organisation that investigates complaints against the police). There are both very detailed legal regulations in some countries while in others there are only generally observed provisions that sometimes are only given in the form of recommendations. A multinational, multiprofessional expert group is required to identify best practices, recommend basic standards of care and identify qualifications which would be appropriate for healthcare professionals working in this field. Highlights: Death and harm is well-recognised in detainees in police custody worldwide. We analyzed the current medical aspects of police custody in European countries. The results reveal significant differences in the regulations among the countries. A multinational expert group is required to recommend basic standards of care.